Psychometric analysis of the Scale of Acdemic Stressors (ECEA), in students of the Catholic University of Santa Maria - Chavez Anaya, Tania Malu (2019)
The purpose of this research is to determine the validity and reliability of the Academic Stressors Scale (ECEA) developed by Cabanach et al. (2016). To this end, this scale was applied to a sample of 150 university students (38 men and 112 women) of the Catholic University of Santa María with an age range of 16 to 32 years. To determine the criterion validity, first, item-scale correlations were performed, obtaining correlation coefficients that are between .429 and .697. The validity of the construct was assessed by exploratory factor analysis with the maximum likelihood method, obtaining a KMO value of .874. By means of the direct Oblimin rotation technique, 12 factors were found, of which, when doing the second factorization, only two factorswere left, which did not confirm the structure of the test proposed by Cabanach et al. However, the Academic Stressors Scale (ECEA) has adequate psychometric properties that make it possible to recommend its use as an instrument for assessing academic stress.